B.P.F.C.® Bio-Plasma® with Pure Growth Factors (BioPlasma®) Used for the Treatment of a Persistent Great Periapical Lesion of an Endodontically Treated Tooth: A New Therapeutic Option - Raffaello Viganò; Mirko Disconzi; Edoardo Bertini; Luca Viganò; Cinzia Casu (Case Reports in Dentistry)
The aim of this case report was to evaluate the efficacy of a new platelet-rich plasma preparation and its regenerative capacity of bone periapical tissue for the treatment of a very compromised endodontic treated tooth, with a periapical lesion of 1.5 cm in diameter, using a pure platelet concentrate. This is made without the use of anticoagulant or any type of activator, e.g., bovine thrombin, calcium chloride. For this reason, it has been called “Pure”; it is the B.P.F.C.® Bio-Plasma® with Pure Growth Factors (BioPlasma®) designed and developed by Dr. Raffaello Viganò. The patient has read and signed a written consent form. The study protocol was approved by the Ethics Committee for Human Studies, University of Varese. X-ray at 2 and 6 months and 4 years after endodontic surgery demonstrated the success of the treatment.